The Training of Beninese Elites in the Eastern countries - (:unkn) unknown (My University, 2021)
The training of African in the eastern countries marked de facto an essential caesura, a “fundamental break” (Koudawo 1992:7) in the academic and political history of African countries. On the one hand the former colonizers are no more the only reference for African countries for elites training. on the other hand, the Soviet project for the training of African elites has deeply changed the history of the elites’ training, but also the international history of student mobility (Eyebiyi and Mazella 2014), institutionalizing until the end of the cold war, a new process of student globalization long before the ERASMUS schemes, the Bologna process, the ESCALA program in Latin America and the other recent policies of massive scholarships granted by some emerging countries. The chapter traces the path of Beninese Elites trained in Eastern countries, especially in Bulgaria. From biographical experiments studying it shows the role of mobility in Elites construction in South during the period 1980-1994.
Keywords: African Research